Ireland : Extended Arrangement-Interim Review Under the Emergency Financing Mechanism. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
The Executive Board approved a three-year Extended Arrangement under the Extended Fund Facility (EFF) for Ireland under the exceptional access policy and Emergency Financing Mechanism (EFM). Political developments have been turbulent. The authorities are moving ahead with a comprehensive strategy to restore confidence in the banking sector. The program objectives for the financial sector, while simple and straightforward, require complex strategies for implementation. Efforts are under way to address data gaps and further strengthen data quality. Robust procedures for program monitoring have been established.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Ireland